Misconception Profile of High School Student on Electrolyte and Non-Electrolyte Solution Using Pictorial-Based Two-Tier Multiple Choices Diagnostic Test - Nahadi Nahadi; Wiwi Siswaningsih; Hanifah Kurnia M (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
The development and study had been done to determine misconceptions profile of class X high school students in Kuningan West Java on electrolyte and non-electrolyte solutions using descriptive methods. The instrument used was a pictorial-based two-tier multiple choices diagnostic test consisted 18 questions. The instrument had been tested for its feasibility with the CVR and CVI values was one, and the Cronbach's Alpha (reliability) value for the whole item was 0.706. The items were applied to class X students in schools with high, medium and low category. Based on the results of the application, the most common misconceptions of students on electrolyte and non-electrolyte solutions was that when dissolved in water, ionic compounds would be ionized into ions, oxygen atom in water molecule interacted with anions and hydrogen atoms in water molecule interacted with cations (37.78%). The misconceptions of class X high school students on electrolyte and non-electrolyte solution in high and low category schools in Kuningan had a significant difference. Based on the one-way ANAVA test, the significance level < 0.05, there was 0.045. The misconception of class X high school students in Kuningan on electrolyte and non-electrolyte solutions based on gender differences did not have a significant difference. Based on results of t test, the significance level > 0.05, there was 0.755.